Commentary: A Citizenship without Social Rights? EU Freedom of Movement and Changing Access to Welfare Rights. (29th January 2020) - Barbulescu, Roxana; Favell, Adrian
Abstract: Despite not being grounded in the classic nation‐building dynamic of citizenship identified by T.H.Marshall, EU citizenship offers social rights and welfare protection to non‐nationals on a principle of non‐discrimination. We narrate a creeping process of retrenchment by which European member states have used policy strategies to undermine this principle, by transforming the unique idea of free movement of persons in the EU to just another form of "immigration" which can be subject to selectivity and exclusion. As Europe's multiple recent crises have unfolded, political resources were found to effect this transformation tangibly via reshaping access to welfare for EU citizens. Focusing on the cases of the UK and Germany, we discuss how, despite their distinctive welfare regimes and labour market systems, these two countries have led the way toward a dismantling of non‐discrimination for EU citizens and effectively the end of the anomalous 'post‐national' dimension of European citizenship.